IFRS (NIIF): an information model at the service of capital markets Eduardo Sosa Mora - Sosa Mora, Eduardo (2021)
This paper addresses the analysis of the changes in the accounting thinking that have been imposed by the IASB (International Accounting Standard Board), through IFRS (International Financial Reporting Standards), over the last decades, in light of the economic transformations on the globalized world.  It is adopted a perspective trascending the technical dimension of accounting and the analysis is placed whitin the economic context on whose borders the accounting practice is carried out.  The alleged neutrality of this discipline is questioned, to support the point of view that the transformations of accounting thinking sponsored by the IASB by means the IFRS, must be understood as a part of the consolidation of the hegemonic power of large transnational companies and the investors operating in international capital markets.